Population Genomics of the Neotropical Brown Stink Bug, Euschistus heros: The Most Important Emerging Insect Pest to Soybean in Brazil - Zucchi, Maria I.; Cordeiro, Erick M. G.; Wu, Xing; Lamana, Letícia Marise; Brown, Patrick J.; Manjunatha, Shilpa; Viana, João Paulo Gomes; Omoto, Celso; Pinheiro, José B.; Clough, Steven J. (Frontiers in Genetics, 2019)
Recent changes in soybean management like the adoption of transgenic crops and no-till farming, in addition to the expansion of cultivated areas into new virgin frontiers, are some of the hypotheses that can explain the rise of secondary pests, such as the Neotropical brown stink bug, Euschistus heros, in Brazil. To better access the risk of increased pests like E. heros and to determine probabilities for insecticide resistance spreading, it is necessary first to access the levels of the genetic diversity, how the genetic diversity is distributed, and how natural selection is acting upon the natural variation. Using the genotyping by sequencing (GBS) technique, we generated ~60,000 single-nucleotide polymorphisms (SNPs) distributed across the E. heros genome to answer some of those questions. The SNP data was used to investigate the pattern of genetic structure, hybridization and natural selection of this emerging pest. We found that E. heros populations presented similar levels of genetic diversity with slightly higher values at several central locations in Brazil. Our results also showed strong genetic structure separating northern and southern Brazilian regions (FST = 0.22; p-value = 0.000) with a very distinct hybrid zone at the central region. The analyses also suggest the possibility that GABA channels and odorant receptors might play a role in the process of natural selection. At least one marker was associated with soybean and beans crops, but no association between allele frequency and cotton was found. We discuss the implications of these findings in the management of emerging pests in agriculture, particularly in the context of large areas of monoculture such as soybean and cotton.